Gender roles, communication, intimacy and marital satisfaction of fisherfolk couples of Brgy. Baybay Norte, Miagao - Nanta, Elna Mariel M.
This sought to describe the marital satisfaction and its contributing factors to the lives of fisherfolk couples. Descriptive statistics and content analysis showed that couples followed traditional gender roles in productive and reproductive activities, demonstrated a combination of "good and bad" quality of communication and high level of intimacy. All these factors contribute to marital satisfaction of the couples. Women experienced multiple burden but they do not perceived this as a negative experience but rather as a part of their "motherhood". Fisherfolk couples dominantly expressed matters concerning their family and relationship. They tend to see verbal communicationas a better way of relaying their message that relying on non-verbal gestures. In terms of intimacy, it was found that they are highly intimate and supportive to each other. With theses findings, fisherfolk couples in general were highly satisfied in their marital relationship.